(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
In the past years, the emigration of population from the Republic of North Macedonia is a highly relevant topic. Special focus is given to the reasons for emigration which are mostly identified as economic reasons, i.e. low income rates, poor living standards, unemployment and poverty. This paper analyzes emigration trends from Western Macedonia, a region that is particularly affected by emigration flows in contemporary Macedonian history. The paper presents detailed statistical data regarding emigrants from Western Macedonia according to gender, origin, marital status, age, reasons for emigration, employment, education, ethnicity, etc. Additionally, the paper will present a research conducted during 2020 regarding migrant families from Western Macedonia, their reasons for emigration, the changes that occurred after the emigration process was completed, life contentment in the new country and the possibility of returning to the homeland.